Tungsten-coated positive electrode material precursor and preparation method thereof, positive electrode material, lithium ion battery and electric equipment
By using tungsten coating technology in the positive electrode material, using a nickel-containing hydroxide core without tungsten and a nickel-containing tungstenite coating, the problems of low capacity performance and poor cycle stability at high voltages in the prior art are solved. It realizes efficient tungsten coated positive electrode material, improving the electrochemical performance and safety of the battery.
Patent Information
- Application Number
- CN202411455464.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-10
AI Technical Summary
The existing cathode materials have low capacity performance and poor cycle stability at high voltages. The island-type cladding leads to stress concentration and cracks, affecting the uniform charging and discharge of the battery and cycle life.
The precursor of the positive electrode material is coated with tungsten-free nickel hydroxide, and the coating layer is nickel-containing tungstenite. It is prepared by co-precipitation reaction to control the thickness and tungsten content of the coating layer to achieve uniform packaging. Cover and efficient isolation.
It improves capacity performance and cycling stability at high voltage, avoids capacity loss caused by tungsten doping, enhances electrochemical performance and safety, and achieves high temperature and high pressure stability of tungsten.
Smart Images

Figure CN119284987A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of positive electrode material precursors, and in particular to a tungsten-coated positive electrode material precursor and a preparation method thereof, positive electrode materials, lithium-ion batteries, and electrical equipment. Background Art
[0002] In recent years, with the rapid development of the electric vehicle industry, the demand for high-energy-density lithium-ion batteries has been increasing. Positive electrode materials are the key to improving the energy density of lithium-ion batteries. The development of positive electrode materials with high specific capacity and long cycle life is crucial to the large-scale development of electric vehicles.
[0003] At present, there are two main ways to dope tungsten on positive electrode materials: one is to dope tungsten as a whole, because the electrical conductivity of tungsten is lower than that of nickel, cobalt, etc., resulting in low capacity under high voltage; the other is to dope tungsten by coating WO3 on the surface of the secondary particles of the precursor, but it will form an island coating (that is, an island-shaped protruding coating layer is formed on the surface of the inner core), resulting in the thickness of the coating layer being too thick or too thin in some parts, making it difficult to achieve uniform coating on the surface, which may lead to inconsistent electrochemical properties of the electrode material, thereby affecting the uniform charge and discharge of the entire battery; the island coating may cause stress concentration in the electrode material during the charge and discharge process, which in turn causes cracks or even fractures, reducing the cycle stability of the battery.
[0004] Based on this, it is of great significance to improve the performance of the precursor to improve the capacity performance and cycle stability of the sintered positive electrode material under high voltage. Summary of the invention
[0005] The purpose of this application is to provide a tungsten-coated positive electrode material precursor and its preparation method, positive electrode material, lithium-ion battery, and electrical equipment to solve the above problems.
[0006] To achieve the above objectives, the first aspect of the present application provides a tungsten-coated positive electrode material precursor, including a core and a coating layer coating the core; the core is a tungsten-free nickel hydroxide, and the coating layer is a nickel-containing tungstate.
[0007] Optionally, the tungsten-coated positive electrode material precursor satisfies at least one of the following conditions:
[0008] A. The tungsten content of the coating layer accounts for 50wt%-60wt% of the total mass of the coating layer;
[0009] B. The chemical formula of the coating layer is: Ni x Co y Mn z M t (OH) 2δ (WO4) 1-δ, wherein x+y+z+t=1, 0≤δ≤0.41, M is at least one of Al, Ti, Zr, Mo, Cr, Mg, Ba, Nb, Y and Sr; optionally, 0.5≤x<1, 0≤y≤0.5, 0≤z≤0.5, 0≤t≤0.1;
[0010] C. The thickness of the coating layer is 0.02 μm-0.5 μm; optionally, the thickness of the coating layer is 0.02 μm-0.25 μm;
[0011] D. The overall tungsten doping amount of the tungsten-coated positive electrode material precursor is 0.1wt%-6.0wt%; optionally, the overall tungsten doping amount of the tungsten-coated positive electrode material precursor is 0.5wt%-5.5wt%;
[0012] E. The chemical formula of the core is: Ni a Co b Mn c M′ d (OH)2; wherein a+b+c+d=1, M′ is at least one of Al, Ti, Zr, Mo, Cr, Mg, Ba, Nb, Y and Sr; optionally, 0.5≤a<1, 0≤b≤0.5, 0≤c≤0.5, 0≤d≤0.1;
[0013] F. The average particle size D50′ of the core is 0.5 μm-19.0 μm; optionally, the average particle size D50′ of the core is 1.0 μm-5.0 μm;
[0014] G. The nickel content of the tungsten-coated positive electrode material precursor accounts for 50 mol%-80 mol% of the total metal content.
[0015] H. The internal porosity of the tungsten-coated positive electrode material precursor is 12%-30%.
[0016] Optionally, the tungsten-coated positive electrode material precursor satisfies at least one of the following conditions:
[0017] A. The primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor are arranged in a staggered manner;
[0018] B. The average length of the primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor is 500 μm-700 μm;
[0019] C. The average width of the primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor is 50 μm-80 μm;
[0020] D. The aspect ratio of the primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor is (6-10):1.
[0021] Optionally, the tungsten-coated positive electrode material precursor satisfies at least one of the following conditions:
[0022] A. The D50 of the tungsten-coated positive electrode material precursor is 1 μm-20 μm; optionally, the D50 of the tungsten-coated positive electrode material precursor is 2 μm-16 μm;
[0023] B. The particle size distribution of the tungsten-coated positive electrode material precursor K90=(D90-D10) / D50 is 0.2-0.6; optionally, K90=(D90-D10) / D50 is 0.35-0.46;
[0024] C. The specific surface area of the tungsten-coated positive electrode material precursor is 12 m 2 / g-16m 2 / g;
[0025] D. The tap density TD of the tungsten-coated positive electrode material precursor is 1.4 g / cm 3 -1.8g / cm 3 .
[0026] The second aspect of the present application provides a method for preparing a tungsten-coated positive electrode material precursor, comprising:
[0027] Putting raw materials including a precipitant solution, a complexing agent solution and water into a first reaction kettle for mixing to obtain a first bottom liquid; adding a nickel-containing solution, the precipitant solution and the complexing agent solution to the first bottom liquid in an oxygen-containing atmosphere to carry out a first coprecipitation reaction to obtain seed crystals;
[0028] The raw materials including the seed crystal, the complexing agent solution and the water are put into a second reaction kettle for mixing to obtain a second base liquid; in an oxygen-containing atmosphere, a nickel-containing solution, a tungstate solution and a complexing agent are added to the second base liquid for a second coprecipitation reaction to obtain a tungsten-coated positive electrode material precursor.
[0029] Optionally, the method for preparing the tungsten-coated positive electrode material precursor satisfies at least one of the following conditions:
[0030] (1) The nickel-containing solution includes nickel salt, and the nickel-containing solution also includes at least one of a cobalt salt solution, a manganese salt solution, and a solution of a doping element M; the total metal content in the nickel salt solution is 1 mol / L-3 mol / L; the doping element M is at least one of Al, Ti, Zr, Mo, Cr, Mg, Ba, Nb, Y and Sr;
[0031] (2) the precipitant solution comprises sodium hydroxide, and the concentration of the precipitant in the precipitant solution is 8 mol / L-12 mol / L;
[0032] (3) the complexing agent solution comprises aqueous ammonia, and the concentration of the complexing agent in the complexing agent solution is 4 mol / L-7 mol / L;
[0033] (4) The tungstate in the tungstate solution includes sodium tungstate and / or ammonium tungstate, and the concentration of the tungstate solution is 0.01 mol / L-0.1 mol / L;
[0034] (5) The tungstate solution also includes a sodium citrate solution, and the concentration of the sodium citrate solution is 0.01 mol / L-0.1 mol / L;
[0035] (6) The pH values of the first base liquid and the second base liquid are 11.2-11.8 respectively;
[0036] (7) The mass fractions of the complexing agent in the first base solution and the second base solution are 2 g / L-10 g / L respectively; when the complexing agent is aqueous ammonia, the mass fraction of the complexing agent refers to the mass of NH3·H2O in the solution, the same below.
[0037] Optionally, the method for preparing the tungsten-coated positive electrode material precursor satisfies at least one of the following conditions:
[0038] (1) controlling the flow rate of the nickel-containing solution in the first coprecipitation reaction to be 3% / h-7% / h of the volume of the reactor;
[0039] (2) controlling the flow ratio of the nickel-containing solution, the precipitant solution and the complexing agent solution in the first coprecipitation reaction to be (0.8-1.2):(0.1-0.6):(0.01-0.1);
[0040] (3) controlling the stirring speed of the first coprecipitation reaction to be 600 rpm-1200 rpm;
[0041] (4) controlling the temperature of the first coprecipitation reaction to be 50° C.-70° C.;
[0042] (5) controlling the pH value of the first coprecipitation reaction to decrease from an initial value of 11.4-12.3 to a stable value of 10.5-11.5, and then maintaining the pH value unchanged;
[0043] (6) controlling the mass fraction of the complexing agent in the first coprecipitation reaction to be 2 g / L-10 g / L;
[0044] (7) the oxygen content of the gas in the first reactor of the first coprecipitation reaction is higher than the oxygen content of the gas in the second reactor of the second coprecipitation reaction;
[0045] (8) controlling the oxygen content of the gas in the first reactor of the first coprecipitation reaction to be 4.0 v%-6.0 v%; wherein the v% value of the oxygen content of the gas in the reactor refers to the volume fraction of oxygen in the gas in the reactor, the same below;
[0046] (9) The average particle size D50′ of the seed crystal is 0.5 μm-19.0 μm; optionally, the average particle size D50′ of the seed crystal is 1.0 μm-15.0 μm;
[0047] (10) controlling the flow rate of the nickel-containing solution in the second coprecipitation reaction to be 2% / h-6% / h of the volume of the reactor;
[0048] (11) controlling the flow ratio of the nickel-containing solution, the tungstate solution and the complexing agent solution in the second coprecipitation reaction to be (0.8-1.2):(0.05-0.2):(0.01-0.08);
[0049] (12) controlling the stirring speed of the second coprecipitation reaction to be 600 rpm-1200 rpm;
[0050] (13) controlling the temperature of the second coprecipitation reaction to be 50° C.-70° C.;
[0051] (14) controlling the pH value of the second coprecipitation reaction to be 10.6-12.1;
[0052] (15) controlling the oxygen content of the gas in the second reaction vessel of the second coprecipitation reaction to be 1.0 v%-3.0 v%;
[0053] (16) The mass fraction of the complexing agent in the second coprecipitation reaction is controlled to be 2 g / L-10 g / L.
[0054] The third aspect of the present application provides a positive electrode material, which is obtained by mixing and sintering the tungsten-coated positive electrode material precursor and a lithium source; the sintering temperature is 900° C.-1000° C., and the sintering time is 10h-20h.
[0055] A fourth aspect of the present application provides a lithium-ion battery, comprising the above-mentioned positive electrode material.
[0056] A fifth aspect of the present application is an electrical device, comprising the lithium-ion battery.
[0057] Compared with the prior art, the beneficial effects of this application include:
[0058] The tungsten-coated positive electrode material precursor provided in the present application has a core that is not doped with tungsten and a coating layer that is a nickel-containing tungstate. Among them, the core is not doped with tungsten, and after being sintered into a positive electrode material to prepare a battery, the capacity loss under high voltage caused by tungsten doping can be avoided; tungsten has good high temperature stability and high voltage stability, and the tungsten in the nickel-containing tungstate in the coating layer exists in the form of tungstate and has a higher tungsten content, and the nickel-containing tungstate is a difficultly soluble substance. After being coated on the surface and sintered into a positive electrode material to prepare a battery, it can be isolated from side reactions with the electrolyte, maintain the stability of the overall structure, and improve the cycle stability and safety under high voltage while taking into account the capacity.
[0059] The preparation method of tungsten-coated positive electrode material precursor provided in the present application uses soluble tungstate as tungsten source during coating, completely or partially replacing conventional alkaline solution such as sodium hydroxide solution as anion source, and can generate an insoluble nickel-containing tungstate-coated core product under alkaline pH conditions. Compared with the island coating layer formed by dry surface coating of tungsten trioxide WO3, the tungsten coating of the product prepared in the present application is more uniform, and the coating layer can be thinner; at the same time, compared with the overall trace tungsten doping, tungsten can be enriched on the surface of the positive electrode material precursor, effectively isolating the electrolyte from reacting with the oxide of the core.
[0060] The present application also effectively realizes controllable oxidation degree of tungsten-coated positive electrode material precursor by controlling oxygen content of gas in the reactor during co-precipitation reaction at different stages, and can prepare a loose core and a thinner coating layer.
[0061] The positive electrode material, lithium-ion battery and electrical equipment provided in this application have high capacity, good cycle performance and excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0063] Figure 1 This is a surface SEM image of the tungsten-coated positive electrode material precursor prepared in Example 1;
[0064] Figure 2 This is a cross-sectional SEM image of the tungsten-coated positive electrode material precursor prepared in Example 1;
[0065] Figure 3 This is the element distribution EMPA diagram of the tungsten-coated positive electrode material precursor prepared in Example 1;
[0066] Figure 4 This is a surface SEM image of the tungsten-coated positive electrode material prepared in Example 1;
[0067] Figure 5 This is the XRD pattern of the tungsten-coated positive electrode material precursor prepared in Example 1;
[0068] Figure 6 This is a surface SEM image of the tungsten-coated positive electrode material precursor prepared in Example 2;
[0069] Figure 7 This is a cross-sectional SEM image of the tungsten-coated positive electrode material precursor prepared in Example 2;
[0070] Figure 8 This is a surface SEM image of the tungsten-coated positive electrode material precursor prepared in Example 3;
[0071] Fig. 9 This is a cross-sectional SEM image of the tungsten-coated positive electrode material precursor prepared in Example 3;
[0072] Fig.10 This is a surface SEM image of the tungsten-coated positive electrode material precursor prepared in Example 4;
[0073] Fig.11 This is a cross-sectional SEM image of the tungsten-coated positive electrode material precursor prepared in Example 4. DETAILED DESCRIPTION
[0074] As used herein:
[0075] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0076] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0077] When an amount, concentration, or other value or parameter is expressed as a range, an optional range, or a range limited by a series of upper and lower optional values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or optional value with any range lower limit or optional value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0078] In these examples, parts and percentages are by mass unless otherwise indicated.
[0079] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0080] In a first aspect, the present application provides a tungsten-coated positive electrode material precursor, comprising a core and a coating layer coating the core; the core is a nickel-containing hydroxide that does not contain tungsten, and the coating layer is a nickel-containing tungstate.
[0081] It should be noted that the core of the tungsten-coated positive electrode material precursor is not doped with tungsten, and the coating layer is nickel-containing tungstate. Among them, the core is not doped with tungsten to avoid the capacity loss under high voltage after sintering into the positive electrode material to prepare the battery due to tungsten doping; the tungsten in the insoluble nickel-containing tungstate in the coating layer exists in the form of tungstate and has a higher tungsten content, which has good high-temperature stability and high-voltage stability. After being coated on the surface and sintered into the positive electrode material to prepare the battery, it can isolate the side reaction with the electrolyte and maintain the stability of the overall structure, while taking into account the capacity and improving the cycle stability and safety under high voltage.
[0082] In some embodiments, the tungsten-coated positive electrode material precursor satisfies at least one of the following conditions:
[0083] A. The tungsten content of the coating layer accounts for 50wt%-60wt% of the total mass of the coating layer;
[0084] Optionally, the tungsten content of the coating layer may account for 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt%, 56wt%, 57wt%, 58wt%, 59wt%, 60wt% or any value between 50wt%-60wt%, 50wt%-54wt%, 54wt%-56wt%, 56wt%-60wt% of the total mass of the coating layer;
[0085] It should be noted that compared with the conventional overall trace tungsten doping, the tungsten content in the precursor coating layer of the present application is very high, that is, the main component of the coating layer is insoluble nickel-containing tungstate. After coating on the surface of the inner core, it can more effectively isolate the sintered positive electrode material from side reactions with the electrolyte after being prepared into a battery, maintain the stability of the overall structure, and thus improve the sintered positive electrode material. Cycle stability and safety under high voltage after being prepared into a battery.
[0086] B. The chemical formula of the coating layer is: Ni x Co y Mn z M t (OH) 2δ (WO4) 1-δ , wherein x+y+z+t=1, 0≤δ≤0.41, M is at least one of Al, Ti, Zr, Mo, Cr, Mg, Ba, Nb, Y and Sr; optionally, 0.5≤x<1, 0≤y≤0.5, 0≤z≤0.5, 0≤t≤0.1;
[0087] Alternatively, in the chemical formula of the coating layer, δ may be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0. 30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, or any value between 0≤δ≤0.05, 0.05≤δ≤0.30, 0.30≤δ≤0.41, 0.20≤δ≤0.35, x can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, or 0.5≤x<1, 0.5 ≤x<0.6, 0.6≤x<0.7, 0.7≤x<0.8, 0.8≤x<0.9, 0.9≤x<1, 0.5≤x<0.65, 0.65≤x<0.85, 0.70≤x<0.95, y can be any value between 0, 0.1, 0.2, 0.3, 0.4, 0.5 or 0≤y≤0.5, 0≤y≤0.1, 0≤y≤0.2, 0≤y≤0.3, 0≤y≤0.4, z can be 0, 0. 1, 0.2, 0.3, 0.4, 0.5 or any value between 0≤z≤0.1, 0≤z≤0.2, 0≤z≤0.3, 0≤z≤0.4, 0≤z≤0.5, t can be any value between 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value between 0≤t≤0.1, 0≤t≤0.01, 0.01≤t≤0.05, 0.05≤t≤0.1;
[0088] In some embodiments, the reaction equation of the second coprecipitation reaction may be:
[0089] xNiSO4+yCoSO4+(1-xy)MnSO4+(1-a)Na2WO4+2aNaOH→
[0090] Ni x Co y Mn 1-x-y (OH) 2a (WO4) 1-a ↓+Na2SO4.
[0091] The nickel-containing tungstate generated in the second coprecipitation reaction is a poorly soluble substance, which is a complex formed by nickel tungstate and one or more of cobalt tungstate, manganese tungstate, nickel hydroxide, cobalt hydroxide, manganese hydroxide, etc.
[0092] It should be noted that the tungsten in the coating layer does not exist in the form of tungsten trioxide WO3, but forms insoluble tungstates with nickel, cobalt, manganese, etc.; compared with the island coating layer formed by tungsten trioxide WO3, the tungsten coating of the product prepared in the present application is more uniform; at the same time, compared with the overall trace tungsten doping, the tungsten content in the coating layer is very high, which can make more tungsten coated on the surface of the inner core in the form of insoluble salts, and will not dissolve in large quantities during post-processing and washing. It can more effectively isolate the sintered positive electrode material from side reactions with the electrolyte after being prepared into a battery, maintain the stability of the overall structure, and thus improve the sintered positive electrode material. Cycle stability and safety under high voltage after being prepared into a battery.
[0093] In some embodiments, the nickel content of the tungsten-coated positive electrode material precursor accounts for 50 mol % to 80 mol % of the total metal content.
[0094] Optionally, the nickel content of the tungsten-coated positive electrode material precursor accounts for 50mol%, 51mol%, 52mol%, 53mol%, 54mol%, 55mol%, 56mol%, 57mol%, 58mol%, 59mol%, 60mol%, 61mol%, 62mol%, 63mol%, 64mol%, 65mol%, 66mol%, 67mol%, 68mol%, 69mol%, 70mol%, 71mol%, 72mol%, 73mol%, 74mol%, 75mol%, 76mol%, 77mol%, 78mol%, 79mol%, 80mol% or any value between 50mol%-70mol%, 50mol%-60mol%, 60mol%-70mol%, 60mol%-80mol%, and 70mol%-80mol% of the total metal content.
[0095] It should be noted that when the nickel content of the tungsten-coated positive electrode material precursor accounts for 50 mol%-80 mol% of the total metal content, it is a medium-nickel ternary positive electrode material precursor, which has a lower cost than the high-nickel precursor. After sintering into a single crystal positive electrode material to prepare a battery, it can release a discharge capacity close to that of the high-nickel precursor under high voltage, and is a low-cost, high-performance positive electrode material precursor.
[0096] C. The chemical formula of the core is: Ni a Co b Mn c M′ d (OH)2; wherein a+b+c+d=1, M′ is at least one of Al, Ti, Zr, Mo, Cr, Mg, Ba, Nb, Y and Sr; optionally, 0.5≤a<1, 0≤b≤0.5, 0≤c≤0.5, 0≤d≤0.1;
[0097] Optionally, in the chemical formula of the kernel, a may be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9 or any value between 0.5≤a<1, 0.5≤a<0.6, 0.6≤a<0.7, 0.7≤a<0.8, 0.8≤a<0.9, 0.9≤a<1, 0.5≤a<0.65, 0.65≤a<0.85, 0.70≤a<0.95, and b may be 0, 0.1, 0.2, 0.3, 0.4, 0.5 or 0≤b≤0.1, 0≤b≤0.2, 0≤b ≤0.3, 0≤b≤0.4, 0≤b≤0.5, c can be 0, 0.1, 0.2, 0.3, 0.4, 0.5 or 0≤c≤0.1, 0≤b≤0.2, 0≤b≤0.3, 0≤b≤0.4, 0≤b≤0.5, d can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or 0≤d≤0.1, 0≤d≤0.01, 0.01≤d≤0.05, 0.05≤d≤0.1;
[0098] Nickel, cobalt and other materials contribute more to the capacity, while tungsten contributes less to the capacity. Compared with the coating layer, the volume of the core accounts for a large proportion. The conductivity of the material deteriorates after sintering into the positive electrode material for the preparation of the battery due to tungsten addition, which has a greater impact on the obstruction of lithium ion transmission. The core is not doped with tungsten, which can avoid the capacity loss of the positive electrode material under high voltage caused by tungsten addition to the core after sintering into the positive electrode material for the preparation of the battery.
[0099] D. The overall tungsten doping amount of the tungsten-coated positive electrode material precursor is 0.1wt%-6.0wt%; optionally, the overall tungsten doping amount of the tungsten-coated positive electrode material precursor is 0.5wt%-5.5wt%;
[0100] Optionally, the overall tungsten doping amount of the positive electrode material precursor can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3.0wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt%, 4.0wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt%, 5.0wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5.9wt%, 6. %. .9wt%, 4.0wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt%, 5.0wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5.9wt%, 6.0wt% or any value between 0.1wt% and 6.0wt%, 0.1wt% and 2.0wt%, 0.1wt% and 1.0wt%, 1.0wt% and 1.8wt%, 1.3wt% and 2.0wt%, 0.1wt% and 2.0wt%, 1.5wt% and 2.5wt%, 2.5wt% and 5.0wt%, 4.0wt% and 5.5wt%;
[0101] It should be noted that when the overall tungsten doping amount of the tungsten-coated positive electrode material precursor is 0.1wt%-6.0wt%, both the capacity and cycle capacity retention rate of the positive electrode material after sintering can be taken into account.
[0102] E. The thickness of the coating layer is 0.02 μm-0.5 μm; optionally, the thickness of the coating layer is 0.02 μm-0.25 μm;
[0103] Optionally, the thickness of the coating layer may be 0.02 μm, 0.05 μm, 0.1 μm, 0.2 μm, 0.3, 0.4 μm, 0.5 μm or any value between 0.02 μm-0.5 μm, 0.02 μm-0.15 μm, 0.15 μm-0.25 μm, 0.25 μm-0.5 μm;
[0104] It should be noted that the coating layer thickness is 0.02μm-0.5μm, which is very thin. This can avoid the loss of capacity performance caused by the obstruction of lithium ion transmission under high voltage after sintering the positive electrode material to prepare the battery due to the coating layer being too thick, and maintain high capacity. If it is less than 0.02μm, it may cause local uneven coating, which will affect the chemical properties of the sintered positive electrode material after it is prepared into a battery.
[0105] F. The average particle size D50′ of the core is 0.5 μm-19.0 μm; optionally, the average particle size D50′ of the core is 1.0 μm-5.0 μm;
[0106] Optionally, the average particle size D50′ of the inner core may be 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or any value between 0.5 μm-19.0 μm, 0.5 μm-15 μm, 0.5 μm-2.5 μm, 2 μm-6 μm, 6 μm-10 μm, 8 μm-15 μm;
[0107] G. The internal porosity of the tungsten-coated positive electrode material precursor is 12%-30%.
[0108] Optionally, the internal porosity of the tungsten-coated positive electrode material precursor can be 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% or any value between 12%-30%, 12%-16%, 16%-20%, 20%-30%, 15%-25%.
[0109] It should be noted that the internal porosity of the tungsten-coated positive electrode material precursor is relatively high, and the loose porous structure is conducive to the penetration of the tungsten coating layer into the core of the positive electrode material precursor, and also promotes the sintering mass transfer of the positive electrode material precursor and the diffusion of lithium ions, which can reduce the sintering temperature and improve the phase uniformity, thus helping to improve the structural stability and safety performance, and can be prepared into a battery to stably exert high capacity at high voltage. For small particles of tungsten-coated positive electrode material precursor, the internal porosity is relatively high, and the loose porous structure promotes the sintering of the positive electrode material precursor into a single crystal positive electrode material, further improving the cycle performance.
[0110] In some embodiments, the tungsten-coated positive electrode material precursor satisfies at least one of the following conditions:
[0111] A. The primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor are arranged in a staggered manner;
[0112] The primary particles of the secondary particles of the tungsten-coated positive electrode material precursor are staggered, and the primary particles are arranged in a disordered manner. More pores can be formed between multiple primary particles, thereby increasing the internal porosity.
[0113] B. The average length of the primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor is 500nm-700nm;
[0114] Optionally, the average length of the primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor may be 500nm, 510nm, 520nm, 530nm, 540nm, 550nm, 560nm, 570nm, 580nm, 590nm, 600nm, 610nm, 620nm, 630nm, 640nm, 650nm, 660nm, 670nm, 680nm, 690nm, 700nm or any value between 500nm-700nm, 500nm-600nm, 600nm-700nm, 550nm-650nm;
[0115] C. The average width of the primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor is 50nm-80nm;
[0116] Optionally, the average width of the primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor may be 50nm, 51nm, 52nm, 53nm, 54nm, 55nm, 56nm, 57nm, 58nm, 59nm, 60nm, 61nm, 62nm, 63nm, 64nm, 65nm, 66nm, 67nm, 68nm, 69nm, 70nm, 71nm, 72nm, 73nm, 74nm, 75nm, 76nm, 77nm, 78nm, 79nm, 80nm or any value between 50nm-80nm, 50nm-60nm, 60nm-70nm, 70nm-80nm, and 55nm-75nm;
[0117] D. The aspect ratio of the primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor is (6-10): 1;
[0118] Optionally, the aspect ratio of the surface primary particles of the secondary particles of the tungsten-coated positive electrode material precursor can be 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, 10:1, or any value between (6-10):1, (6-7):1, (7-8):1, (8-9):1, and (7.5-8.9):1.
[0119] It should be noted that the length, width and aspect ratio of the primary particles of the secondary particles of the tungsten-coated positive electrode material precursor are large, and are arranged in a staggered manner, so that the secondary particles have a large number of large pores on the surface, which is conducive to the penetration of the electrolyte after sintering into the positive electrode material to prepare the battery.
[0120] In some embodiments, the tungsten-coated positive electrode material precursor satisfies at least one of the following conditions:
[0121] A. The D50 of the tungsten-coated positive electrode material precursor is 1 μm-20 μm; optionally, the D50 of the tungsten-coated positive electrode material precursor is 2 μm-16 μm;
[0122] Optionally, the D50 of the tungsten-coated positive electrode material precursor may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm or any value between 1 μm and 20 μm; Optionally, the D50 of the tungsten-coated positive electrode material precursor may be 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4 .5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, 15μm, 15.5μm, 16μm or any value between 2μm-16μm, 2μm-6μm, 6μm-10μm, 8μm-15μm;
[0123] D50 is the particle size corresponding to when the cumulative particle size distribution number of a sample reaches 50%;
[0124] It should be noted that the tungsten-coated cathode material precursor with a D50 of 2μm-6μm can also be sintered into single crystals to further improve the cycle performance of the battery after being sintered into cathode materials;
[0125] B. The particle size distribution of the tungsten-coated positive electrode material precursor K90=(D90-D10) / D50 is 0.2-0.6; optionally, K90=(D90-D10) / D50 is 0.35-0.46;
[0126] D10 is the particle size corresponding to when the cumulative particle size distribution number of a sample reaches 10%;
[0127] D50 is the particle size corresponding to when the cumulative particle size distribution number of a sample reaches 50%;
[0128] D90 is the particle size corresponding to when the cumulative particle size distribution number of a sample reaches 90%;
[0129] K90: It means the calculated value of particle size distribution width, which is used to characterize the uniformity of material particle size;
[0130] Optionally, the particle size distribution K90=(D90-D10) / D50 of the tungsten-coated positive electrode material precursor can be 0.2, 0.3, 0.4, 0.5, 0.6 or any value between 0.2-0.6; Optionally, the particle size distribution K90=(D90-D10) / D50 of the tungsten-coated positive electrode material precursor can be 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46 or any value between 0.35-0.46;
[0131] The tungsten-coated positive electrode material precursor provided by the present application controls the pH value during the first coprecipitation reaction, thereby having a lower initial nucleation amount (a small number of secondary particles are generated and the particle size is larger), and a lower growth rate ratio, so that the precursor particle size distribution is narrower and the secondary particle size consistency is better, thereby avoiding the degradation of cycle performance due to overburning during sintering. Among them, the nucleation amount refers to the number and particle size of the generated secondary particles. When the conditions are consistent, the total amount of hydroxide generated is constant, the secondary particle size is large, and the number of secondary particles is small; conversely, the number of secondary particles is large, and the particle size of the secondary particles is small.
[0132] C. The specific surface area of the tungsten-coated positive electrode material precursor is 12 m 2 / g-16m 2 / g;
[0133] Optionally, the specific surface area BET of the tungsten-coated cathode material precursor can be 12 m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g or 12m 2 / g-16m 2 / g, 12m 2 / g-13m 2 / g, 13m 2 / g-14m 2 / g, 14m 2 / g-16m 2 / g, 12m 2 / g-15m 2 Any value between / g;
[0134] It should be noted that, combined with the internal porosity of the tungsten-coated positive electrode material precursor, the specific surface area within the above range can ensure a high structural stability, which is beneficial to improving the capacity performance of the battery after sintering the positive electrode material.
[0135] D. The tap density TD of the tungsten-coated positive electrode material precursor is 1.4 g / cm 3 -1.8g / cm 3 .
[0136] Optionally, the tap density TD of the tungsten-coated positive electrode material precursor may be 1.4 g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 or 1.4g / cm 3 -1.8g / cm 3 , 1.4g / cm 3 -1.6g / cm 3 , 1.6g / cm 3 -1.8g / cm 3 Any value in between.
[0137] It should be noted that the tap density within the range can ensure high structural stability, which is beneficial to improving the compaction density of the positive electrode material.
[0138] The tungsten-coated positive electrode material precursor secondary particles involved in this application can be qualitatively determined by electron probe microanalysis (EPMA) to determine the distribution of nickel, cobalt, manganese, and tungsten elements in the core and coating layer, respectively. For example, the distribution of Ni, Mn, Co, and W elements in the tungsten-coated positive electrode material precursor secondary particles prepared in Example 1 is as follows: Figure 3 As shown: Figure 3 (d) The primary particles in the lower left corner are arranged radially, which is the local cross-sectional morphology of the secondary particles. The primary particles in the middle area are arranged in a circular shape, which is the surface morphology of the secondary particles. Figure 3 (a) Figure 3 (b) Figure 3 (c) Figure 3 (e) Content distribution diagrams of Ni, Mn, Co, and W elements in the same local cross section of secondary particles and on the surface of secondary particles, respectively; Figure 3 (f) is the W element distribution diagram of the secondary particle surface after repeated measurement; Figure 3 It can be seen that:
[0139] ① Figure 3 (a) Figure 3 (b) Figure 3The scattered points representing the element contents of Ni, Mn, and Co in the local cross-sectional area of the secondary particles in the lower left corner of (c) all show a trend of red→yellow→green→blue from the inside to the outside, that is, the corresponding element contents decrease in sequence, which is consistent with the chemical formula of the coating layer and the chemical formula of the core in Example 1;
[0140] ② Figure 3 (a) Figure 3 (b) Figure 3 The scatter plot of the Ni, Mn and Co element contents corresponding to the local cross-sectional area of the secondary particles in the lower left corner of (c) all have blue circles on the outermost side, and the corresponding contents are all low. It can be inferred that the blue circles are coating layers with low Ni, Mn and Co contents; and the proportion of the blue circles is very small. Referring to the 1 μm scale length, the thickness of the blue circles is <0.1 μm, which is consistent with the coating thickness calculated by half of the difference between the average particle size D50 of the secondary particles and the average particle size D50′ of the seed crystal (kernel) in Example 1;
[0141] ③ Figure 3 In (e), most of the scattered points of the W element are blue, and a small number are green; Figure 3 In (f), most of the scattered points of W element are blue and green, with very small amounts of red and yellow, indicating that the actual W content is low, which is far from the test value of ICP-MS. The reason is that W may show low sensitivity and poor signal response in elemental analysis EMPA; it can only qualitatively characterize that W may exist on the surface of the cathode material precursor.
[0142] ④ In addition, some of the primary particles of the tungsten-coated cathode material precursor may be broken due to production, transportation, testing, etc., causing the primary particle fragments to spread to the surrounding area. Figure 3 In (e), the background also has sparse blue scattered points of W elements.
[0143] The test methods for the content of secondary particles D50, D10, D90, BET, TD, and metal elements (such as nickel, cobalt, manganese, tungsten, zirconium, etc.) of the tungsten-coated positive electrode material precursor involved in this application are as follows:
[0144] D50 (average particle size), D10, D90: measured by laser particle size tester (instrument model: Mastersizer 3000);
[0145] BET (specific surface area): measured by fully automatic nitrogen adsorption specific surface area analyzer (instrument model: BELPREP-VACII / BELSORP-MINI-X);
[0146] TD (tap density): measured by a powder tap density tester (model: Dandong Better BT-302);
[0147] Contents of nickel, cobalt, manganese, tungsten, zirconium, etc.: measured by inductively coupled plasma mass spectrometry (ICP-MS, instrument model: Agilent 7850ICP-MS).
[0148] The test method of the primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor involved in this application is: select the SEM photo of the secondary particle surface of the tungsten-coated positive electrode material precursor with the largest magnification, and take the longest straight-line distance between the two ends of the selected surface primary particle in the surface SEM photo as the length, and take the longest straight-line distance between the two ends perpendicular to the length line as the width, and use the electronic ruler software ruler to measure, and obtain the length and width of multiple surface primary particles, and then calculate the aspect ratio of multiple surface primary particles respectively; finally, calculate the average length, average width, and average aspect ratio of multiple surface primary particles respectively. In the above measurement, if there is a situation where a primary particle is blocked, the unblocked part is assumed to be a complete primary particle for measurement. Exemplarily, the magnification of the surface SEM photo can be 40.0K, 50.0K, etc.
[0149] The specific test method for the internal porosity of the secondary particles of the tungsten-coated positive electrode material precursor involved in this application is: adjust the magnification of the scanning electron microscope (SEM) until there is only one complete cross section of the secondary particles of the tungsten-coated positive electrode material precursor in the view and take a picture to obtain a SEM picture, and then use the Image-Pro Plus software to analyze the cross-sectional SEM picture and calculate the internal porosity. The calculation formula is: internal porosity = [(the sum of the areas of the pores of the secondary particles in the cross section / the cross-sectional area of the secondary particles) × 100] (%). Exemplarily, the magnification of the cross-sectional SEM photo can be 20.0K, 25.0K, etc. The specific magnification is preferably such that there is only one complete or nearly complete single secondary particle sphere cross section in the SEM field of view.
[0150] There are two testing methods for the average thickness of the coating layer of the secondary particles of the tungsten-coated positive electrode material precursor involved in this application:
[0151] Method 1: Take the seed crystals and product samples of the same batch to measure D50' and D50 respectively, and calculate the average thickness of the coating layer as (average particle size D50 of secondary particles - average particle size D50' of seed crystals (kernel)) ÷ 2; illustratively, the calculation process of the coating layer thickness in Example 1 is:
[0152]
[0153] Method 2: In a scanning electron microscope cross-sectional photograph (SEM cross-sectional photograph) / transmission electron microscope cross-sectional photograph (TEM cross-sectional photograph), measure the coating layer thickness of multiple cross-sectional secondary particles, and the average thickness is the arithmetic mean of the thicknesses of multiple coating layers; illustratively, the multiple number can be 10, 20, etc., and the magnification of the SEM cross-sectional photograph / TEM cross-sectional photograph is 50.0K, 100.0K, 150.0K, etc. The specific magnification is preferably based on the field of view of the photograph to facilitate measurement of the coating layer.
[0154] The core of the secondary particles of the tungsten-coated positive electrode material precursor involved in the present application does not contain tungsten, and the coating layer contains tungsten, that is, the mass content of tungsten in the coating layer is the mass of tungsten in the precursor divided by the total mass of the coating layer; illustratively, the secondary particles are set to be spherical in an ideal state, and the density of the secondary particles of the tungsten-coated positive electrode material precursor is the same as the density of the coating layer. The calculation process of the tungsten content of the coating layer of the secondary particles of the tungsten-coated positive electrode material precursor in Example 1 is:
[0155]
[0156] The coating layer molecular formula of the secondary particles of the tungsten-coated positive electrode material precursor involved in the present application is first calculated by the mass content of nickel, cobalt and manganese obtained by ICP-MS test to calculate the molar ratio of nickel, cobalt and manganese, and then calculated by the coating layer thickness and the overall tungsten doping amount of the tungsten-coated positive electrode material precursor; illustratively, the calculation process of the molar content of tungstate in the coating layer molecular formula of Example 1 is: The molar ratio of nickel, cobalt and manganese in the coating layer molecular formula of the precursor secondary particles
[0157]
[0158] It can be calculated that δ is 0.28, and the molecular formula of the coating layer is Ni 0.65 Co 0.06 Mn 0.29 (OH) 0.56 (WO4) 0.72 .
[0159] Note: Sodium hydroxide solution is not added in the coating preparation method, but the molecular formula of the coating contains hydroxide ions. The reason is presumed to be that the second base liquid is alkaline, and some hydroxide ions in the reaction system during the second coprecipitation reaction also participate in the reaction to generate nickel-containing tungstate, which is a basic salt compound.
[0160] The second aspect of the present application provides a method for preparing a tungsten-coated positive electrode material precursor, comprising:
[0161] Putting raw materials including a precipitant solution, a complexing agent solution and water into a first reaction kettle for mixing to obtain a first bottom liquid; adding a nickel-containing solution, the precipitant solution and the complexing agent solution to the first bottom liquid in an oxygen-containing atmosphere to carry out a first coprecipitation reaction to obtain seed crystals;
[0162] The raw materials including the seed crystal, the complexing agent solution and the water are put into a second reaction kettle for mixing to obtain a second base liquid; in an oxygen-containing atmosphere, a nickel-containing solution, a tungstate solution and a complexing agent solution are added to the second base liquid for a second coprecipitation reaction to obtain a tungsten-coated positive electrode material precursor.
[0163] The preparation method of tungsten-coated positive electrode material precursor provided by the present application uses soluble tungstate as tungsten source during coating, completely or partially replacing conventional alkaline solution such as sodium hydroxide solution as anion source, and can generate insoluble nickel-containing tungstate-coated core products under alkaline pH conditions, and the coating layer can be thinner. Compared with the island coating layer formed by dry surface coating of tungsten trioxide WO3, the tungsten coating of the product prepared by the present application is more uniform; at the same time, compared with the overall trace tungsten doping, tungsten can be enriched on the surface of the positive electrode material precursor, effectively isolating the electrolyte from reacting with the oxide of the core.
[0164] The present application also effectively realizes controllable oxidation degree of tungsten-coated positive electrode material precursor by controlling the oxygen content of the gas in the reactor during the co-precipitation reaction at different stages, and can prepare a loose core and a thinner coating layer.
[0165] In some embodiments, the method for preparing the tungsten-coated positive electrode material precursor satisfies at least one of the following conditions:
[0166] (1) The nickel-containing solution includes nickel salt, and the nickel-containing solution also includes at least one of a cobalt salt solution, a manganese salt solution, and a solution of a doping element M; the total metal content in the nickel salt solution is 1 mol / L-3 mol / L; the doping element M is at least one of Al, Ti, Zr, Mo, Cr, Mg, Ba, Nb, Y and Sr;
[0167] Optionally, the total metal content in the nickel salt solution may be 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L or any value between 1 mol / L and 3 mol / L;
[0168] (2) the precipitant solution comprises sodium hydroxide, and the concentration of the precipitant in the precipitant solution is 8 mol / L-12 mol / L;
[0169] Optionally, the concentration of the precipitant in the precipitant solution may be 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L, 12 mol / L or any value between 8 mol / L and 12 mol / L;
[0170] (3) the complexing agent solution comprises aqueous ammonia, and the concentration of the complexing agent in the complexing agent solution is 4 mol / L-7 mol / L;
[0171] Optionally, the concentration of the complexing agent in the complexing agent solution may be 4 mol / L, 4.5 mol / L, 5 mol / L, 5.5 mol / L, 6 mol / L, 6.5 mol / L, 7 mol / L or any value between 4 mol / L and 7 mol / L;
[0172] (4) The tungstate in the tungstate solution includes sodium tungstate and / or ammonium tungstate, and the concentration of the tungstate solution is 0.01 mol / L-0.1 mol / L;
[0173] Optionally, the concentration of the tungstate solution may be 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L or any value between 0.01 mol / L and 0.1 mol / L;
[0174] (5) The tungstate solution also includes a sodium citrate solution, and the concentration of the sodium citrate solution is 0.01 mol / L-0.1 mol / L;
[0175] Optionally, the concentration of the sodium citrate solution can be 0.01mol / L, 0.02mol / L, 0.03mol / L, 0.04mol / L, 0.05mol / L, 0.06mol / L, 0.07mol / L, 0.08mol / L, 0.09mol / L, 0.1mol / L or any value between 0.01mol / L and 0.1mol / L;
[0176] (6) The pH values of the first base liquid and the second base liquid are 11.2-11.8 respectively;
[0177] Optionally, the pH values of the first base liquid and the second base liquid may be 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8 or any value between 11.2 and 11.8;
[0178] It should be noted that the first base solution within the pH range can ensure that the nucleation amount meets the requirements and that the reaction cycle meets the requirements.
[0179] (7) The mass fractions of the complexing agent in the first base liquid and the second base liquid are 2 g / L-10 g / L respectively.
[0180] Optionally, the mass fraction of the complexing agent in the first base liquid and the second base liquid can be 2g / L, 3g / L, 4g / L, 5g / L, 6g / L, 7g / L, 8g / L, 9g / L, 10g / L or any value between 2g / L and 10g / L.
[0181] In some embodiments, the method for preparing the tungsten-coated positive electrode material precursor satisfies at least one of the following conditions:
[0182] (1) controlling the flow rate of the nickel-containing solution in the first coprecipitation reaction to be 3% / h-7% / h of the volume of the reactor;
[0183] Optionally, the flow rate of the nickel-containing solution in the first coprecipitation reaction is controlled to be 3% / h, 4% / h, 5% / h, 6% / h, 7% / h or any value between 3% / h and 7% / h of the volume of the reactor;
[0184] (2) controlling the flow ratio of the nickel-containing solution, the precipitant solution and the complexing agent solution in the first coprecipitation reaction to be (0.8-1.2):(0.1-0.6):(0.01-0.1);
[0185] Optionally, the flow ratio of the nickel-containing solution, the precipitant solution and the complexing agent solution in the first coprecipitation reaction can be controlled to be 0.8:0.1:0.01, 0.9:0.1:0.01, 1.0:0.1:0.01, 1.1:0.1:0.01, 1.2:0.1:0.01, 0.8:0.2:0.01, 0.8:0.3:0.01, 0.8:0. 3: 0.01, 0.8: 0.5: 0.01, 0.8: 0.6: 0.01, 0.8: 0.1: 0.02, 0.8: 0.1: 0.04, 0.8: 0.1: 0.06, 0.8: 0.1: 0.08, 0.8: 0.1: 0.1 or any value between (0.8-1.2): (0.1-0.6): (0.01-0.1);
[0186] It should be noted that the flow ratio within the range can achieve a more appropriate pH and ammonia concentration, ensuring the stable progress of the first coprecipitation reaction; controlling the flow rate of the nickel-containing solution can control the reaction time and the porosity of the inner core of the obtained precursor secondary particles.
[0187] (3) controlling the stirring speed of the first coprecipitation reaction to be 600 rpm-1200 rpm;
[0188] Optionally, the stirring speed of the first coprecipitation reaction is controlled to be 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm or any value between 600 rpm and 1200 rpm;
[0189] (4) controlling the temperature of the first coprecipitation reaction to be 50° C.-70° C.;
[0190] Optionally, the temperature of the first coprecipitation reaction may be controlled to be 50°C, 55°C, 60°C, 65°C, 70°C or any value between 50°C and 70°C;
[0191] (5) controlling the pH value of the first coprecipitation reaction to decrease from an initial value of 11.4-12.3 to a stable value of 10.5-11.5, and then maintaining the pH value unchanged;
[0192] Optionally, the initial pH value of the first coprecipitation reaction may be 11.4, 11.5, 11.6, 11.7, 11.8, 11.9, 12.0, 12.1, 12.2, 12.3 or any value between 11.4 and 12.3, and then the pH value may be reduced to 10.8, 10.9, 11.0, 11.1, 11.2 or any value between 10.8 and 11.2, 10.5 and 11.5;
[0193] It should be noted that a higher pH value is conducive to the formation of larger primary particles. By gradually reducing the pH value during the first coprecipitation reaction and then maintaining stability, it is possible to ensure that the first coprecipitation reaction proceeds stably, and that the secondary particles of the seed crystals prepared by the first coprecipitation reduce or avoid the generation of fine primary particles, and maintain a certain internal porosity, particle size and sphericity of the secondary particles.
[0194] (6) controlling the mass fraction of the complexing agent in the first coprecipitation reaction to be 2 g / L-10 g / L;
[0195] Optionally, the mass fraction of the complexing agent controlling the first coprecipitation reaction may be 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L or any value between 2 g / L and 10 g / L;
[0196] (7) the oxygen content of the gas in the first reactor of the first coprecipitation reaction is higher than the oxygen content of the gas in the second reactor of the second coprecipitation reaction;
[0197] The oxygen content of the gas in the first reactor of the first coprecipitation reaction is higher, which can increase the oxidation degree of the primary particles and form a core that is looser than the coating layer.
[0198] (8) controlling the oxygen content of the gas in the first reaction vessel of the first coprecipitation reaction to be 4.0 v%-6.0 v%;
[0199] Optionally, the oxygen content of the gas in the first reactor of the first coprecipitation reaction is controlled to be 4.0v%, 4.1v%, 4.2v%, 4.3v%, 4.4v%, 4.5v%, 4.6v%, 4.7v%, 4.8v%, 4.9v%, 5.0v%, 5.1v%, 5.2v%, 5.3v%, 5.4v%, 5.5v%, 5.6v%, 5.7v%, 5.8v%, 5.9v%, 6.0v% or any value between 4.0v% and 6.0v%;
[0200] (9) The average particle size D50′ of the seed crystal is 0.5 μm-19.0 μm; optionally, the average particle size D50′ of the seed crystal is 1.0 μm-15.0 μm;
[0201] Optionally, the average particle size D50′ of the seed crystals may be 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or any value between 0.5 μm and 19.0 μm; Optionally, the average particle size D50′ of the seed crystals may be 1 μm, 1.5 μm, 2 μm m, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10 μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, 15μm or any value between 1.0μm and 15μm;
[0202] (10) controlling the flow rate of the nickel-containing solution in the second coprecipitation reaction to be 2% / h-6% / h of the volume of the reactor;
[0203] Optionally, the flow rate of the nickel-containing solution in the second coprecipitation reaction can be controlled to be 2% / h, 2.5% / h, 3% / h, 3.5% / h, 4% / h, 4.5% / h, 5% / h, 5.5% / h, 6% / h or any value between 2% / h and 6% / h of the volume of the reactor;
[0204] (11) controlling the flow ratio of the nickel-containing solution, the tungstate solution and the complexing agent solution in the second coprecipitation reaction to be (0.8-1.2):(0.05-0.2):(0.01-0.08);
[0205] Optionally, the flow ratio of the nickel-containing solution, the tungstate solution and the complexing agent solution in the second coprecipitation reaction can be controlled to be 0.8:0.05:0.01, 0.9:0.05:0.01, 1.0:0.05:0.01, 1.1:0.05:0.01, 1.2:0.05:0.01, 0.8:0.1:0.01, 0.8:0.15:0.01, 0.8:0.2: 0.01, 0.8:0.05:0.02, 0.8:0.05:0.03, 0.8:0.05:0.04, 0.8:0.05:0.05, 0.8:0.05:0.06, 0.8:0.05:0.07, 0.8:0.05:0.08 or any value between (0.8-1.2):(0.05-0.2):(0.01-0.08);
[0206] It should be noted that a flow ratio within the above range can achieve a more appropriate pH value and ammonia concentration, while ensuring that the tungsten content meets the requirements.
[0207] (12) controlling the stirring speed of the second coprecipitation reaction to be 600 rpm-1200 rpm;
[0208] Optionally, the stirring speed of the second coprecipitation reaction is controlled to be 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm or any value between 600 rpm and 1200 rpm;
[0209] (13) controlling the temperature of the second coprecipitation reaction to be 50° C.-70° C.;
[0210] Optionally, the temperature of the second coprecipitation reaction may be controlled to be 50°C, 55°C, 60°C, 65°C, 70°C or any value between 50°C and 70°C;
[0211] (14) controlling the pH value of the second coprecipitation reaction to be 10.6-12.1;
[0212] Optionally, the pH value of the second coprecipitation reaction can be controlled to be 10.6, 10.7, 10.8, 10.9, 11.0, 11.1, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9, 12.0, 12.1 or any value between 10.6 and 12.1;
[0213] It should be noted that the pH value within the above range can ensure that the second coprecipitation reaction proceeds stably and that the tungsten content meets the requirements.
[0214] (15) controlling the oxygen content of the gas in the second reaction vessel of the second coprecipitation reaction to be 1.0 v%-3.0 v%;
[0215] Optionally, the oxygen content of the gas in the second reactor of the second coprecipitation reaction is controlled to be 1.0v%, 1.1v%, 1.2v%, 1.3v%, 1.4v%, 1.5v%, 1.6v%, 1.7v%, 1.8v%, 1.9v%, 2.0v%, 2.1v%, 2.2v%, 2.3v%, 2.4v%, 2.5v%, 2.6v%, 2.7v%, 2.8v%, 2.9v%, 3.0v% or any value between 1.0v% and 3.0v%;
[0216] The oxygen content of the gas during the reaction will affect the size and arrangement of the primary particles, and thus affect the thickness of the coating layer.
[0217] (16) controlling the mass fraction of the complexing agent in the second coprecipitation reaction to be 2 g / L-10 g / L;
[0218] Optionally, the mass fraction of the complexing agent controlling the second coprecipitation reaction can be 2g / L, 3g / L, 4g / L, 5g / L, 6g / L, 7g / L, 8g / L, 9g / L, 10g / L or any value between 2g / L and 10g / L.
[0219] The third aspect of the present application provides a positive electrode material obtained by mixing and sintering the tungsten-coated positive electrode material precursor and a lithium source.
[0220] In some embodiments, the sintering temperature is 900° C.-1000° C., and the sintering time is 10 h-20 h.
[0221] It should be noted that for small particles at this sintering temperature, the grain growth rate is accelerated. When the primary particles grow to a certain size, the agglomerated polycrystalline secondary particles will automatically disintegrate to form single crystal positive electrode materials. At this sintering time, the single crystal particle size and alkali residue are more suitable.
[0222] A fourth aspect of the present application provides a lithium-ion battery, comprising the above-mentioned positive electrode material.
[0223] A fifth aspect of the present application is an electrical device, comprising the lithium-ion battery.
[0224] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0225] Example 1
[0226] This embodiment provides a method for preparing a tungsten-coated positive electrode material precursor, comprising:
[0227] S1: Prepare an ammonia solution with a mass fraction of 5.5 mol / L; prepare a sodium hydroxide solution with a mass fraction of 10.8 mol / L; weigh nickel sulfate, cobalt sulfate, and manganese sulfate to prepare a nickel-containing solution with a molar ratio of Ni:Co:Mn=65:6:29 and a total metal content of 2 mol / L; weigh sodium tungstate and sodium citrate to prepare a tungstate solution with a sodium tungstate concentration of 0.03 mol / L and a sodium citrate concentration of 0.015 mol / L, which is a mixed solution of sodium tungstate-sodium citrate;
[0228] S2: mixing sodium hydroxide solution, ammonia solution and water in a first reaction kettle to obtain a first bottom liquid with a pH value of 11.6, wherein the mass fraction of ammonia solution in the first bottom liquid is 8 g / L;
[0229] S3: introducing an oxygen-containing atmosphere composed of nitrogen and air, and controlling the oxygen content of the gas in the first reactor to be 4.8v%-5.2v%; adding a nickel-containing solution, a sodium hydroxide solution and an ammonia solution to the first bottom liquid for a first coprecipitation reaction, during the reaction, controlling the flow ratio of the nickel-containing solution, the sodium hydroxide solution and the ammonia solution to be 1:(0.36-0.38):(0.04-0.05), the flow rate of the nickel-containing solution to be 5.8% / h-6.2% / h of the volume of the first reactor, the initial pH value is 11.6, which decreases to 11.3 after 9h of reaction, and decreases to 11.0-11.2 after 12h of reaction, and then maintaining the pH value unchanged, the mass fraction of ammonia water is 8g / L, the stirring speed is 1000rpm, and the reaction temperature is 60°C, until the seed crystals of the target particle size are obtained;
[0230] S4: introducing an oxygen-containing atmosphere composed of nitrogen and air, and controlling the oxygen content of the gas in the first reactor to be 2.4v%-2.6v%; mixing the seed crystals, ammonia solution and water in the second reactor to obtain a second bottom liquid with a pH value of 11.5, wherein the mass fraction of ammonia solution in the second bottom liquid is 7g / L;
[0231] S5: Add nickel-containing solution, tungstate solution and ammonia solution to the second base liquid for a second coprecipitation reaction. During the reaction, the flow ratio of nickel-containing solution, tungstate solution and ammonia solution is controlled to be 1: (0.09-0.10): (0.04-0.05), the flow rate of nickel-containing solution is 3.8% / h-4.0% / h of the volume of the second reactor, the mass fraction of ammonia water is 8g / L, the pH value is maintained at 11.2-11.4, the stirring speed is 600rpm, and the temperature is 60°C, until a tungsten-coated positive electrode material precursor of the target particle size is obtained, and then washed, dried, sieved, demagnetized and packaged to obtain a finished product.
[0232] The surface SEM of the tungsten-coated positive electrode material precursor prepared in this example is as follows Figure 1 shown.
[0233] Cross-sectional SEM of tungsten-coated cathode material precursor Figure 2 shown.
[0234] The distribution state of each element in the tungsten-coated cathode material precursor is as follows: Figure 3 shown.
[0235] The XRD pattern of the tungsten-coated positive electrode material precursor prepared in this example is as follows: Figure 5 shown.
[0236] The molar ratio of nickel, cobalt and manganese was calculated by the mass content of nickel, cobalt and manganese obtained by ICP-MS test, and then the molecular formula of the coating layer was calculated by the coating thickness and tungsten content of the coating layer: Ni 0.65 Co 0.06 Mn 0.29 (OH) 0.56 (WO4) 0.72 .
[0237] Since the content of nickel-containing tungstate in the tungsten-coated cathode material precursor is low and near the detection limit of the XRD signal, the corresponding peak of nickel-containing tungstate is very small; and since there is no standard card for nickel-containing tungstate, the XRD standard card of nickel tungstate, which is a component with a higher content in nickel-containing tungstate, was selected for comparison. Figure 5 It can be seen that there is a peak type corresponding to nickel tungstate. Therefore, combined with the calculated molecular formula of the coating layer, it can be explained that the coating layer is mainly coated with nickel tungstate.
[0238] A third aspect of this embodiment provides a method for preparing a positive electrode material, comprising:
[0239] The tungsten-coated positive electrode material precursor and lithium hydroxide are mixed to obtain a mixed lithium material, wherein the molar ratio of Li:(Ni+Co+Mn) in the mixed lithium material is 1.05:1, and then the mixed lithium material is sintered at 900°C in oxygen for 15 hours to obtain the positive electrode material.
[0240] The surface SEM of the positive electrode material prepared in this example is as follows Figure 4 shown.
[0241] Example 2
[0242] This embodiment provides a method for preparing a tungsten-coated positive electrode material precursor, comprising:
[0243] S1: Prepare an ammonia solution with a mass fraction of 5.5 mol / L; prepare a sodium hydroxide solution with a mass fraction of 10.8 mol / L; weigh nickel sulfate, cobalt sulfate, and manganese sulfate to prepare a nickel-containing solution with a molar ratio of Ni:Co:Mn=69.5:6.5:24 and a total metal content of 2 mol / L; weigh sodium tungstate and sodium citrate to prepare a tungstate solution with a sodium tungstate concentration of 0.05 mol / L and a sodium citrate concentration of 0.025 mol / L;
[0244] S2: mixing sodium hydroxide solution, ammonia solution and water in a first reaction kettle to obtain a first bottom liquid with a pH value of 11.6, wherein the mass fraction of ammonia solution in the first bottom liquid is 8 g / L;
[0245] S3: introducing an oxygen-containing atmosphere composed of nitrogen and air, and controlling the oxygen content of the gas in the first reactor to be 4.7v%-5.1v%; adding a nickel-containing solution, a sodium hydroxide solution and an ammonia solution to the first bottom liquid for a first coprecipitation reaction, during the reaction, controlling the flow ratio of the nickel-containing solution, the sodium hydroxide solution and the ammonia solution to be 1:(0.36-0.38):(0.04-0.05), the flow rate of the nickel-containing solution to be 5.7% / h-6.1% / h of the volume of the first reactor, the initial pH value is 11.6, which decreases to 11.4 after 9h of reaction, and decreases to 10.9-11.1 after 12h of reaction, and then maintaining the pH value unchanged, the mass fraction of ammonia water is 8g / L, the stirring speed is 1000rpm, and the reaction temperature is 60°C, until the seed crystals of the target particle size are obtained;
[0246] S4: introducing an oxygen-containing atmosphere composed of nitrogen and air, and controlling the oxygen content of the gas in the first reactor to be 1.8v%-2.0v%; mixing the seed crystals, ammonia solution and water in the second reactor to obtain a second bottom liquid with a pH value of 11.5, wherein the mass fraction of ammonia solution in the second bottom liquid is 7g / L;
[0247] S5: Add nickel-containing solution, tungstate solution and ammonia solution to the second base liquid for a second coprecipitation reaction. During the reaction, the flow ratio of the nickel-containing solution, tungstate solution and ammonia solution is controlled to be 1: (0.09-0.10): (0.04-0.05), the flow rate of the nickel-containing solution is 3.9% / h-4.1% / h of the volume of the second reactor, the mass fraction of ammonia water is 8g / L, the pH value is maintained at 11.2-11.4, the stirring speed is 600rpm, and the temperature is 60°C, until a tungsten-coated positive electrode material precursor of the target particle size is obtained, and then washed, dried, sieved, demagnetized and packaged to obtain a finished product.
[0248] A third aspect of this embodiment provides a method for preparing a positive electrode material, comprising:
[0249] The tungsten-coated positive electrode material precursor and lithium hydroxide are mixed to obtain a mixed lithium material, wherein the molar ratio of Li:(Ni+Co+Mn) in the mixed lithium material is 1.05:1, and then the mixed lithium material is sintered at 900°C in oxygen for 15 hours to obtain the positive electrode material.
[0250] The surface SEM of the tungsten-coated positive electrode material precursor prepared in this example is as follows Figure 6 shown.
[0251] Cross-sectional SEM of tungsten-coated cathode material precursor Figure 7 shown.
[0252] Example 3
[0253] This embodiment provides a method for preparing a tungsten-coated positive electrode material precursor, comprising:
[0254] S1: Prepare an ammonia solution with a mass fraction of 5.5 mol / L; prepare a sodium hydroxide solution with a mass fraction of 10.8 mol / L; weigh nickel sulfate, cobalt sulfate, manganese sulfate, and zirconium sulfate to prepare a nickel-containing solution with a molar ratio of Ni:Co:Mn:Zr=69.5:12:18:0.5 and a total metal content of 2 mol / L; weigh sodium tungstate and sodium citrate to prepare a tungstate solution with a sodium tungstate concentration of 0.08 mol / L and a sodium citrate concentration of 0.04 mol / L, which is a mixed solution of sodium tungstate-sodium citrate;
[0255] S2: Mixing sodium hydroxide solution, ammonia solution and water in a first reaction kettle to obtain a first bottom liquid with a pH value of 11.7. The mass fraction of ammonia water in the first bottom liquid is 4.5 g / L.
[0256] S3: introducing an oxygen-containing atmosphere composed of nitrogen and air, and controlling the oxygen content of the gas in the first reactor to be 5.8v%-6.0v%; adding a nickel-containing solution, a sodium hydroxide solution and an ammonia solution to the first bottom liquid for a first coprecipitation reaction, during the reaction, controlling the flow ratio of the nickel-containing solution, the sodium hydroxide solution and the ammonia solution to be 1:(0.35-0.37):(0.04-0.05), the flow rate of the nickel-containing solution to be 4.8% / h-5.0% / h of the volume of the first reactor, the pH value to be 11.7 initially, reduced to 11.4 after 4h of reaction, reduced to 10.9-11.1 after 7h of reaction, and then maintaining the pH value unchanged, the mass fraction of ammonia water to be 4.5g / L, the stirring speed to be 1000rpm, the reaction temperature to be 60°C, until the seed crystals of the target particle size are obtained;
[0257] S4: introducing an oxygen-containing atmosphere composed of nitrogen and air, and controlling the oxygen content of the gas in the first reactor to be 1.4v%-1.6v%; mixing the seed crystals, ammonia solution and water in the second reactor to obtain a second bottom liquid with a pH value of 11.0, wherein the mass fraction of ammonia solution in the second bottom liquid is 4g / L;
[0258] S5: Add nickel-containing solution, tungstate solution and ammonia solution to the second base liquid for a second coprecipitation reaction. During the reaction, the flow ratio of the nickel-containing solution, tungstate solution and ammonia solution is controlled to be 1: (0.05-0.06): (0.04-0.05), the flow rate of the nickel-containing solution is 3.0% / h-3.2% / h of the volume of the second reactor, the mass fraction of ammonia water is 4g / L, the pH value is maintained at 10.8-11.0, the stirring speed is 600rpm, and the temperature is 60°C, until a tungsten-coated positive electrode material precursor of the target particle size is obtained, and then washed, dried, sieved, demagnetized and packaged to obtain a finished product.
[0259] A third aspect of this embodiment provides a method for preparing a positive electrode material, comprising:
[0260] The tungsten-coated positive electrode material precursor and lithium hydroxide are mixed to obtain a mixed lithium material, wherein the molar ratio of Li:(Ni+Co+Mn+Zr) in the mixed lithium material is 1.05:1, and then the mixed lithium material is sintered at 950°C in oxygen for 15 hours to obtain the positive electrode material.
[0261] The surface SEM of the tungsten-coated positive electrode material precursor prepared in this example is as follows Figure 8 shown.
[0262] Cross-sectional SEM of tungsten-coated cathode material precursor Fig. 9 shown.
[0263] Example 4
[0264] This embodiment provides a method for preparing a tungsten-coated positive electrode material precursor, comprising:
[0265] S1: Prepare an ammonia solution with a mass fraction of 5.5 mol / L; prepare a sodium hydroxide solution with a mass fraction of 10.8 mol / L; weigh nickel sulfate, cobalt sulfate, and manganese sulfate to prepare a nickel-containing solution with a molar ratio of Ni:Co:Mn=60:12:28 and a total metal content of 2 mol / L; weigh sodium tungstate and sodium citrate to prepare a tungstate solution with a sodium tungstate concentration of 0.08 mol / L and a sodium citrate concentration of 0.04 mol / L, which is a mixed solution of sodium tungstate-sodium citrate;
[0266] S2: Mixing sodium hydroxide solution, ammonia solution and water in a first reaction kettle to obtain a first bottom liquid with a pH value of 11.4. The mass fraction of ammonia solution in the first bottom liquid is 4.5 g / L.
[0267] S3: introducing an oxygen-containing atmosphere composed of nitrogen and air, and controlling the oxygen content of the gas in the first reactor to be 5.8v%-6.0v%; adding a nickel-containing solution, a sodium hydroxide solution and an ammonia solution to the first bottom liquid for a first coprecipitation reaction, during the reaction, controlling the flow ratio of the nickel-containing solution, the sodium hydroxide solution and the ammonia solution to be 1:(0.36-0.38):(0.04-0.05), the flow rate of the nickel-containing solution to be 4.9% / h-5.1% / h of the volume of the first reactor, the initial pH value is 11.4, and after reacting for 34 hours, it is reduced to 10.8-11.0, and then the pH value is maintained unchanged, the mass fraction of ammonia water is 4.5g / L, the stirring speed is 800rpm, and the reaction temperature is 60°C, until the seed crystals of the target particle size are obtained;
[0268] S4: introducing an oxygen-containing atmosphere composed of nitrogen and air, and controlling the oxygen content of the gas in the first reactor to be 1.5v%-1.7v%; mixing the seed crystals, ammonia solution and water in the second reactor to obtain a second bottom liquid with a pH value of 10.5, wherein the mass fraction of ammonia solution in the second bottom liquid is 4g / L;
[0269] S5: Add nickel-containing solution, tungstate solution and ammonia solution to the second base liquid for a second coprecipitation reaction. During the reaction, the flow ratio of the nickel-containing solution, tungstate solution and ammonia solution is controlled to be 1: (0.04-0.05): (0.04-0.05), the flow rate of the nickel-containing solution is 3.0% / h-3.2% / h of the volume of the second reactor, the mass fraction of ammonia water is 4g / L, the pH value is maintained at 10.6-10.8, the stirring speed is 600rpm, and the temperature is 60°C, until a tungsten-coated positive electrode material precursor of the target particle size is obtained, and then washed, dried, sieved, demagnetized and packaged to obtain a finished product.
[0270] A third aspect of this embodiment provides a method for preparing a positive electrode material, comprising:
[0271] The tungsten-coated positive electrode material precursor and lithium hydroxide are mixed to obtain a mixed lithium material, wherein the molar ratio of Li:(Ni+Co+Mn) in the mixed lithium material is 1.05:1, and then the mixed lithium material is sintered at 950°C in oxygen for 15 hours to obtain the positive electrode material.
[0272] The surface SEM of the tungsten-coated positive electrode material precursor prepared in this example is as follows Fig.10 shown.
[0273] Cross-sectional SEM of tungsten-coated cathode material precursor Fig.11 shown.
[0274] Example 5 (different sintering conditions)
[0275] This comparative example provides a polycrystalline positive electrode material, which is different from Example 1 in that the sintering temperature of this comparative example is 750° C., the sintering time is 12 h, and the other conditions are consistent with Example 1.
[0276] Comparative Example 1 (without tungsten coating)
[0277] This comparative example provides a method for preparing a positive electrode material precursor, wherein only the first coprecipitation reaction is performed, and the second coprecipitation reaction is not performed. The specific steps are as follows:
[0278] S1: Same as Example 1;
[0279] S2: mixing sodium hydroxide solution, ammonia solution and water in a reaction kettle to obtain a base liquid with a pH value of 11.9, and a mass fraction of ammonia water in the base liquid is 7 g / L;
[0280] S3: introducing an oxygen-containing atmosphere composed of nitrogen and air, and controlling the oxygen content of the gas in the first reactor to be 4.8v%-5.2v%; adding a nickel-containing solution, a sodium hydroxide solution and an ammonia solution to the base liquid for co-precipitation reaction, during the reaction, controlling the flow ratio of the nickel-containing solution, the sodium hydroxide solution and the ammonia solution to be 1:(0.36-0.38):(0.04-0.05), the flow rate of the nickel-containing solution to be 4.0% / h-4.2% / h of the reactor volume, the initial pH value to be 11.9, after reacting for 9h, it decreases to 11.1-11.3, and then maintaining the pH value unchanged, the mass fraction of ammonia water to be 8g / L, the stirring speed to be 1000rpm, the reaction temperature to be 60°C, until a cathode material precursor with a target particle size is obtained.
[0281] The third aspect of this comparative example provides a method for preparing a positive electrode material, comprising:
[0282] 100 g of positive electrode material precursor and lithium hydroxide were mixed to obtain a mixed lithium material, in which the molar ratio of Li: (Ni+Co+Mn) in the mixed lithium material was 1.05:1, and then the mixed lithium material was sintered at 900° C. in oxygen for 15 hours to obtain the positive electrode material.
[0283] Comparative Example 2 (Uniformly Doped with Tungsten)
[0284] This comparative example provides a method for preparing a positive electrode material precursor, which is different from Example 1 in that tungsten in this comparative example is uniformly doped throughout the positive electrode material precursor, and the specific steps are as follows:
[0285] S1: Same as Example 1;
[0286] S2: mixing sodium hydroxide solution, ammonia solution and water in the first reaction kettle to obtain a base liquid with a pH value of 11.6, and a mass fraction of ammonia water in the base liquid is 7 g / L;
[0287] S3: introducing an oxygen-containing atmosphere composed of nitrogen and air, and controlling the oxygen content of the gas in the first reactor to be 8.0v%-8.2v%; adding a nickel-containing solution, a tungstate solution, a sodium hydroxide solution and an ammonia solution to the bottom liquid for coprecipitation reaction, during the reaction, controlling the flow ratio of the nickel-containing solution, the tungstate solution, the sodium hydroxide solution and the ammonia solution to be 1:(0.4-0.6):(0.36-0.38):(0.04-0.05), the flow rate of the nickel-containing solution is 7.8% / h-8.2% / h of the volume of the first reactor, the mass fraction of ammonia water is 8g / L, the initial pH value is 11.6, and it decreases to 11.3-11.5 after reacting for 9h, and then maintaining the pH value unchanged, the stirring speed is 1000rpm, and the temperature is 45°C, until a cathode material precursor of the target particle size is obtained, and then washed, dried, sieved, demagnetized and packaged to obtain a finished product.
[0288] The third aspect of this comparative example provides a method for preparing a positive electrode material, comprising:
[0289] 100 g of positive electrode material precursor and lithium hydroxide were mixed to obtain a mixed lithium material, in which the molar ratio of Li: (Ni+Co+Mn) in the mixed lithium material was 1.05:1, and then the mixed lithium material was sintered at 900° C. in oxygen for 15 hours to obtain the positive electrode material.
[0290] Comparative Example 3 (coating layer is tungsten trioxide)
[0291] This comparative example provides a positive electrode material, which is different from Example 1 in that the positive electrode material precursor prepared in Comparative Example 1 is used as a raw material for preparation in the comparative example, and the specific steps are as follows:
[0292] Nitrogen was introduced, and the oxygen content of the gas in the first reactor was controlled to be less than 1.0v%; 1L of 1mol / L lithium hydroxide solution was added to 100g of the positive electrode material precursor prepared in Comparative Example 1, and the mixture was stirred at a low speed to obtain a solution A, and then 2.45wt% of tungsten trioxide by weight of the precursor was added to the solution A to obtain a slurry B; the slurry B was evaporated and crystallized at 90°C until the slurry was dry to obtain a coated product, and then the obtained crystalline product was mixed with lithium, and lithium hydroxide was mixed to obtain a mixed lithium material, wherein the molar ratio of Li:(Ni+Co+Mn) in the mixed lithium material was 1.05:1, and then the mixed lithium material was sintered at 900°C in oxygen for 15h to obtain the positive electrode material.
[0293] Comparative Example 4 (Changing the reaction conditions during the first coprecipitation reaction)
[0294] This comparative example provides a positive electrode material precursor and a preparation method thereof, and a positive electrode material, which differs from Example 1 in that in step S3 of preparing the positive electrode material precursor, the flow rate of the nickel-containing solution is 0.9% / h-1.1% / h of the volume of the first reactor, and other conditions are consistent with Example 1. By reducing the flow rate of the nickel-containing solution, a denser inner core can be generated.
[0295] Comparative Example 5 (Changing the reaction conditions during the second coprecipitation reaction)
[0296] This comparative example provides a positive electrode material precursor and a preparation method thereof, and a positive electrode material, which differs from Example 1 in that in the S4 step of preparing the positive electrode material precursor in this comparative example, the flow rate of the nickel-containing solution during the second coprecipitation reaction is 0.9% / h-1.1% / h of the volume of the second reactor, and other conditions are consistent with Example 1. By reducing the flow rate of the nickel-containing solution, a denser inner core can be generated.
[0297] Comparative Example (Direct Preparation of Nickel-Containing Tungstate)
[0298] This comparative example provides a method for preparing nickel-containing tungstate and a composition analysis of the nickel-containing tungstate.
[0299] The first aspect of this comparative example provides a method for preparing a nickel-containing tungstate, comprising:
[0300] S1: Prepare an ammonia solution with a mass fraction of 5.5 mol / L; prepare a sodium hydroxide solution with a mass fraction of 10.8 mol / L; weigh nickel sulfate, cobalt sulfate, and manganese sulfate to prepare a nickel-containing solution with a molar ratio of Ni:Co:Mn=65:6:29 and a total metal content of 2 mol / L; weigh sodium tungstate and sodium citrate to prepare a tungstate solution with a sodium tungstate concentration of 0.03 mol / L and a sodium citrate concentration of 0.015 mol / L;
[0301] S2: introducing an oxygen-containing atmosphere composed of nitrogen and air, and controlling the oxygen content of the gas in the reactor to be 2.4v%-2.6v%; mixing the seed crystals, ammonia solution and water in the reactor to obtain a base liquid with a pH value of 11.5, wherein the mass fraction of ammonia solution in the base liquid is 7g / L;
[0302] S3: Add nickel-containing solution, tungstate solution and ammonia solution to the base liquid for co-precipitation reaction. During the reaction, the flow ratio of nickel-containing solution, tungstate solution and ammonia solution is controlled to be 1: (0.09-0.10): (0.04-0.05), the flow rate of nickel-containing solution is 3.8% / h-4.0% / h of the volume of the second reactor, the mass fraction of ammonia water is 8g / L, the pH value is maintained at 11.2-11.4, the stirring speed is 600rpm, the temperature is 60°C, the reaction time is kept consistent with Example 1, and then washed, dried, sieved, demagnetized and packaged to obtain a finished product.
[0303] Composition detection method of nickel-containing tungstate: Dissolve the sample with a mixed acid of concentrated hydrochloric acid and concentrated nitric acid in a volume ratio of 3:1, and then measure the Ni content by ICP instrument to be 15.33wt%, Co content to be 1.45wt%, Mn content to be 6.32wt%, and W content to be 53.93wt%, that is, the molecular formula of nickel-containing tungstate is Ni 0.65 Co 0.06 Mn 0.29 (OH) 0.56 (WO4) 0.72 .
[0304] The precursors prepared in the above examples and comparative examples were tested for parameters such as D50, K90, BET, and TD. The specific results are shown in Table 1.
[0305] Table 1 Precursor test data 1
[0306]
[0307] The precursors prepared in the above-mentioned embodiments and comparative examples were tested for the average particle size D50′ of the core, the thickness of the coating layer, and the internal porosity. The specific results are shown in Table 2.
[0308] Table 2 Precursor test data 2
[0309]
[0310]
[0311] The average length, average width and average aspect ratio of the primary particles of the secondary particles of the tungsten-coated positive electrode material precursor prepared in the above examples and comparative examples were tested, and the specific results are shown in Table 3.
[0312] Table 3 Precursor test data 3
[0313]
[0314] The positive electrode materials prepared in the above examples and comparative examples were subjected to electrochemical performance tests, and the specific results are shown in Table 4.
[0315] The electrochemical performance test method of this application is as follows: The button battery model used in this application is a CR-2032 half-cell. The battery is composed of a positive electrode plate, a negative electrode plate (metal lithium), a diaphragm (Celgard-2325), a gasket, a spring and an electrolyte. Then charge and discharge at room temperature (3.0-4.3V and 3.0-4.5V), and test the capacity retention rate of 100 cycles at 1C current, 1C = 190mAh / g.
[0316] Table 4 Performance test of positive electrode materials
[0317]
[0318]
[0319] The tungsten-coated positive electrode material precursor provided in the present application has a core that is not doped with tungsten, and a coating layer that is an insoluble nickel-containing tungstate. Among them, the core is not doped with tungsten to avoid the capacity loss of the obtained positive electrode material under high voltage caused by tungsten doping; the tungsten in the coating layer exists in the form of tungstate and has a higher tungsten content, and has good high-voltage stability. The positive electrode material sintered after being coated on the surface of the core can isolate the side reactions with the electrolyte, maintain the stability of the overall structure, and improve the cycle stability under high voltage while taking into account the capacity. In particular, the low-cost medium-nickel precursor prepared in Example 1-4 released a higher discharge capacity at a high voltage of 4.5V, reaching more than 210mAh / g. The product prepared in Example 1-3 is a small particle, which is a single-crystal small-particle positive electrode material after high-temperature sintering, and has better cycle performance at 4.5V under high voltage. Compared with the small-particle single-crystal ternary positive electrode materials obtained after sintering in Examples 1-3, the large-particle polycrystalline ternary positive electrode materials obtained after sintering in Example 4 and the small-particle polycrystalline ternary positive electrode materials obtained after sintering in Example 5 all show slightly higher initial discharge capacities, but slightly lower capacity retention rates after multiple cycles. Therefore, this application has a very broad prospect for industrial application.
[0320] In Comparative Example 1, no tungsten doping or tungsten coating was performed, and the cycle capacity retention rate was poor, especially at a high voltage of 4.5V, due to the escape of a large number of lithium ions, the lithium-nickel mixing was aggravated, and the cycle capacity retention rate dropped significantly; in Comparative Example 2, the cycle capacity retention rate of the doped precursor prepared by the method of uniformly doping tungsten was higher than that of Comparative Example 1, but the total amount of doped tungsten was higher, resulting in a lower capacity, and the cycle capacity retention rate of Comparative Example 2 after uniformly doping tungsten was also significantly lower than that of Examples 1-4 with surface-coated tungsten; Comparative Example 3 was sintered by mixing tungsten trioxide at the back end on the basis of Comparative Example 1, but its capacity retention rate and cycle capacity retention rate were both low; in Comparative Example 4, the flow rate in the reaction process was reduced on the basis of Example 1, the reaction period was extended, the particle size growth was slowed down, and the internal structure was dense, resulting in a low capacity performance of the battery prepared by the sintered positive electrode material; in Comparative Example 5, the flow rate in the coating stage was reduced on the basis of Example 1, and the coating layer was dense, which also resulted in a low capacity and could not meet the long-range requirements.
[0321] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0322] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A tungsten-coated positive electrode material precursor, characterized in that: It comprises a core and a coating layer covering the core; the core is a nickel-containing hydroxide without tungsten, and the coating layer is a nickel-containing tungstate.
2. The tungsten-coated positive electrode material precursor according to claim 1, characterized in that: At least one of the following conditions is met: A. The tungsten content of the coating layer accounts for 50wt%-60wt% of the total mass of the coating layer; B. The chemical formula of the coating layer is: Ni x Co y Mn z M t (OH) 2δ (WO4) 1-δ , wherein x+y+z+t=1, 0≤δ≤0.41, M is at least one of Al, Ti, Zr, Mo, Cr, Mg, Ba, Nb, Y and Sr; optionally, 0.5≤x<1, 0≤y≤0.5, 0≤z≤0.5, 0≤t≤0.1; C. The thickness of the coating layer is 0.02 μm-0.5 μm; optionally, the thickness of the coating layer is 0.02 μm-0.25 μm; D. The overall tungsten doping amount of the tungsten-coated positive electrode material precursor is 0.1wt%-6.0wt%; optionally, the overall tungsten doping amount of the tungsten-coated positive electrode material precursor is 0.5wt%-5.5wt%; E. The chemical formula of the core is: Ni a Co b Mn c M′ d (OH)2; wherein a+b+c+d=1, M′ is at least one of Al, Ti, Zr, Mo, Cr, Mg, Ba, Nb, Y and Sr; optionally, 0.5≤a<1, 0≤b≤0.5, 0≤c≤0.5, 0≤d≤0.1; F. The average particle size D50′ of the core is 0.5 μm-19.0 μm; optionally, the average particle size D50′ of the core is 1.0 μm-5.0 μm; G. The internal porosity of the tungsten-coated positive electrode material precursor is 12%-30%.
3. The tungsten-coated positive electrode material precursor according to claim 1, characterized in that: At least one of the following conditions is met: A. The primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor are arranged in a staggered manner; B. The average length of the primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor is 500nm-700nm; C. The average width of the primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor is 50nm-80nm; D. The aspect ratio of the primary particles on the surface of the secondary particles of the tungsten-coated positive electrode material precursor is (6-10):
1.
4. The tungsten-coated positive electrode material precursor according to claim 1, characterized in that: At least one of the following conditions is met: A. The D50 of the tungsten-coated positive electrode material precursor is 1 μm-20 μm; optionally, the D50 of the tungsten-coated positive electrode material precursor is 2 μm-6 μm; B. The particle size distribution of the tungsten-coated positive electrode material precursor K90=(D90-D10) / D50 is 0.2-0.6; optionally, K90=(D90-D10) / D50 is 0.35-0.46; C. The specific surface area of the tungsten-coated positive electrode material precursor is 12 m 2 / g-16m 2 / g; D. The tap density TD of the tungsten-coated positive electrode material precursor is 1.4 g / cm 3 -1.8g / cm 3 .
5. A method for preparing a tungsten-coated positive electrode material precursor, characterized in that: include: Putting raw materials including a precipitant solution, a complexing agent solution and water into a first reaction kettle for mixing to obtain a first bottom solution; In an oxygen-containing atmosphere, adding a nickel-containing solution, the precipitant solution and the complexing agent solution to the first base solution to perform a first coprecipitation reaction to obtain seed crystals; The raw materials including the seed crystal, the complexing agent solution and the water are put into a second reaction kettle for mixing to obtain a second base liquid; in an oxygen-containing atmosphere, a nickel-containing solution, a tungstate solution and a complexing agent solution are added to the second base liquid for a second coprecipitation reaction to obtain a tungsten-coated positive electrode material precursor.
6. The method for preparing a tungsten-coated positive electrode material precursor according to claim 5, characterized in that: At least one of the following conditions is met: (1) The nickel-containing solution includes nickel salt, and the nickel-containing solution also includes at least one of a cobalt salt solution, a manganese salt solution, and a solution of a doping element M; the total metal content in the nickel salt solution is 1 mol / L-3 mol / L; the doping element M is at least one of Al, Ti, Zr, Mo, Cr, Mg, Ba, Nb, Y and Sr; (2) the precipitant solution comprises sodium hydroxide, and the molar concentration of the precipitant in the precipitant solution is 8 mol / L-12 mol / L; (3) the complexing agent solution comprises aqueous ammonia, and the molar concentration of the complexing agent in the complexing agent solution is 4 mol / L-7 mol / L; (4) The tungstate in the tungstate solution includes sodium tungstate and / or ammonium tungstate, and the concentration of the tungstate solution is 0.01 mol / L-0.1 mol / L; (5) The tungstate solution also includes a sodium citrate solution, and the concentration of the sodium citrate solution is 0.01 mol / L-0.1 mol / L; (6) The pH values of the first base liquid and the second base liquid are 11.2-11.8 respectively; (7) The mass fractions of the complexing agent in the first base liquid and the second base liquid are 2 g / L-10 g / L respectively.
7. The method for preparing a tungsten-coated positive electrode material precursor according to claim 5 or 6, characterized in that: At least one of the following conditions is met: (1) controlling the flow rate of the nickel-containing solution in the first coprecipitation reaction to be 3% / h-7% / h of the volume of the reactor; (2) controlling the flow ratio of the nickel-containing solution, the precipitant solution and the complexing agent solution in the first coprecipitation reaction to be (0.8-1.2):(0.1-0.6):(0.01-0.1); (3) controlling the stirring speed of the first coprecipitation reaction to be 600 rpm-1200 rpm; (4) controlling the temperature of the first coprecipitation reaction to be 50° C.-70° C.; (5) controlling the pH value of the first coprecipitation reaction to decrease from an initial value of 11.4-12.3 to a stable value of 10.5-11.5, and then maintaining the pH value unchanged; (6) controlling the mass fraction of the complexing agent in the first coprecipitation reaction to be 2 g / L-10 g / L; (7) the oxygen content of the gas in the first reactor of the first coprecipitation reaction is higher than the oxygen content of the gas in the second reactor of the second coprecipitation reaction; (8) controlling the oxygen content of the gas in the first reaction vessel of the first coprecipitation reaction to be 4.0 v%-6.0 v%; (9) The average particle size D50′ of the seed crystal is 0.5 μm-19.0 μm; optionally, the average particle size D50′ of the seed crystal is 1.0 μm-5.0 μm; (10) controlling the flow rate of the nickel-containing solution in the second coprecipitation reaction to be 2% / h-6% / h of the volume of the reactor; (11) controlling the flow ratio of the nickel-containing solution, the tungstate solution and the complexing agent solution in the second coprecipitation reaction to be (0.8-1.2):(0.05-0.2):(0.01-0.08); (12) controlling the stirring speed of the second coprecipitation reaction to be 600 rpm-1200 rpm; (13) controlling the temperature of the second coprecipitation reaction to be 50° C.-70° C.; (14) controlling the pH value of the second coprecipitation reaction to be 10.6-12.1; (15) controlling the oxygen content of the gas in the second reaction vessel of the second coprecipitation reaction to be 1.0 v%-3.0 v%; (16) The mass fraction of the complexing agent in the second coprecipitation reaction is controlled to be 2 g / L-10 g / L.
8. A positive electrode material, characterized in that The tungsten-coated positive electrode material precursor according to any one of claims 1 to 3 is mixed with a lithium source and sintered; the sintering temperature is 900° C.-1000° C., and the sintering time is 10 h-20 h.
9. A lithium ion battery, characterized in that: Comprising the positive electrode material as claimed in claim 8.
10. An electrical equipment, characterized in that: Includes the lithium ion battery as claimed in claim 9.